Numerical investigation of non-equilibrium condensation of wet stem. - Kavabata, Luccas Koji (2022)
The present MSc dissertation is a part of the supersonic separator project of the Research Center for Gas Innovation (RCGI) of the Polytechnic School of the University of São Paulo. The project aims at researching and developing a supersonic separator which should remove most of the 2 contained in natural gas. This is desired since such a device would allow the exploration of natural gas reserves with high 2 content given that nowadays the separation process (or processes) involved is rather expensive. The main goal of this research is to investigate the physical consistency of the metastable condensation models available on the branch of the Stanford University Unstructured (SU2) for high-speed condensing flows of a pure vapor under low- and high-pressure conditions in a Laval nozzle. It is also a subject of interest of this research to analyze the entropy generation associated with metastable condensation phenomena which occurs due to the fact that the liquid and vapor phases exchange thermal energy under while being at different temperatures, i.e., heat exchange with temperature difference. Additionally a brief analysis on how the position of the condensation wave is affect by the stagnation conditions has also been performed. The evolution of the liquid phase is evaluated with the use of the method of moments, which replace the continuity equation for the liquid and evaluate statistical quantities such as the average liquid droplet radius, average liquid surface, and average liquid volume, whereas the conservation equations are written for the vapor phase. The nucleation and growth rate models employed were the factor f correction and Hills growth rate model, respectively. The results obtained from the numerical simulations have shown that the code is able to predict the occurrence of metastable condensation within a certain degree of accuracy. However, the use of the saturation temperature as the trigger for metastable condensation may lead to inaccurate and physically inconsistent results. It has also been found that the process of metastable condensation generates entropy, which is an important aspect to be taken into account in the design of a supersonic separator owing to the fact that this irreversibility cannot be avoided given that metastable condensation must occur in order for the device to be able to remove 2 from natural gas.